Lexical Convergence and Semantic Variation between Cebuano and Hiligaynon: Evidence from Scripted Spoken Discourse in the Philippines - Jerelyn Aberia Labio; Gennicel Olbenario; Flora Mie Ellena; Jolli Me Villahermosa (RSF Press, 2026)
This study examines lexical convergence and semantic variation between Cebuano and Hiligaynon in the Philippines, focusing on shared terminologies in scripted spoken discourse. Despite their close geographical and cultural proximity, few studies have systematically explored how these languages converge and diverge in vocabulary and meaning in context. The corpus consisted of recorded radio dramas from DYHB RMN Bacolod and DYHP RMN Cebu, specifically Handumanan sa Isa ka Ambalahon and Handumanan sa Usa ka Awit. Terminologies were collected through manual qualitative coding using a researcher-developed tally sheet and validated by expert native speakers to ensure analytical trustworthiness. Guided by descriptive, qualitative content analysis and structural analysis within an established qualitative discourse-analytic and translation studies framework, the study examined semantic nuances and grammatical function, stress patterns, and contextual use of shared lexical items. Findings indicate significant yet non-uniform lexical convergence, with some terms exhibiting parallel meanings across both languages while others show semantic variation influenced by grammatical function, stress patterns, and discourse context. These results suggest that, although Cebuano and Hiligaynon share a linguistic heritage, shared lexical forms do not always yield equivalent meanings. By foregrounding meaning-in-use in scripted spoken discourse, the study extends prior qualitative and discourse-based analyses of Philippine languages, contributing to a deeper understanding of lexical convergence and semantic variation, and offering theory-informed implications for multilingual education, instructional material development, and effective communication in linguistically diverse contexts.